Characterisation of pulp and paper manufactured from oil palm empty fruit bunches and kenaf fibres - Dahlan, Rafidah; Mohamed @ Asa'ari, Ainun Zuriyati; Abdullah, Hazwani Husna; Ibrahim, Rushdan; Abdullah, Luqman Chuah; Adnan, Sharmiza; Md. Tahir, Paridah; Harun, Jalaluddin (Universiti Putra Malaysia Press, 2017)
In papermaking, blending or mixture of fibres is one of the ways to enhance mechanical properties of paper. The objective of this study was to evaluate the properties of paper manufactured from mixture of oil palm empty fruit bunch (EFB) and kenaf fibres. The papers were prepared according to 10, 30, 50 and 70 percentages of kenaf whole stem blended into oil palm empty fruit bunch fibres. The preparation and testing of papers were carried out based on TAPPI Test Methods. Results showed that using kenaf whole stem fibres improved the mechanical properties of the blended papers and complied with the standard requirement for writing and printing grade paper.